Periodontal Wound Healing and Tissue Regeneration: A Narrative Review - Young-Dan Cho; Kyoung-Hwa Kim; Yong-Moo Lee; Young Ku; Yang-Jo Seol (MDPI AG, 2021)
Periodontal disease is a major public health issue, and various periodontal therapies have been performed to regenerate periodontal tissues. The periodontium is a complex structure composed of specialized tissues that support the teeth, and most periodontal surgeries are invasive procedures, including a resection of the gingiva or the alveolar bone. The periodontal wound healing process is slightly different from cutaneous wound healing and is similar to fetal healing, being almost scar-free. The aim of this review article is to provide an overview of periodontal wound healing and discuss various surgical and pharmaceutical approaches to achieve stable wound healing and improve the treatment outcomes. In addition, detrimental and limiting factors that induce a compromised prognosis are discussed, along with the perspective and future direction for successful periodontal tissue regeneration.